Mulheres em campo: novas reflexões acerca do feminino no futebol - Stahlberg, Lara Tejada (2011)
Football has been known as an arena marked by masculinity, but in a very particular manner, mainly heterosexual. That could be explained through the way the game has been constructed, in a defined performance focused on what would be inheriting to a condition of what is ideally understood to be a man. In that context, the conformation of the bodies to the practice of football in many countries, especially Brazil, induced the idea that it a sport that is neither suitable nor desirable to the female body. Therefore, the women have been reduced to spectators and their entry in that universe restricted to what could be considers appropriate to a woman. However, we have witnessed a continuous subversion of that space and its representations, which goes from the amount of women in stadiums to the number of women who have professionally inserted themselves in many areas in the sport, insofar as if football can be understood as an institution that for some thinkers expresses the Brazilian society on the symbolic plan, understanding the role played by women in that universe and in what way that space is occupied can be very relevant. In that sense, the study of such roles, as players, referees, journalists and supporters may reveal different nuances of a new spectrum of representations formulated by old and new actors that operate in that space.